Toward a More Robust and Efficient Usability Testing Method of Clinical Decision Support for Nurses Derived From Nursing Electronic Health Record Data. Issue 4 (24th June 2016) - Lopez, Karen Dunn; Febretti, Alessandro; Stifter, Janet; Johnson, Andrew; Wilkie, Diana J.; Keenan, Gail
Abstract : PURPOSE: To develop methods for rapid and simultaneous design, testing, and management of multiple clinical decision support (CDS) features to aid nurse decision‐making. METHODS: We used quota sampling, think‐aloud and cognitive interviews, and deductive and inductive coding of synchronized audio video data and archival libraries. FINDINGS: Our methods and organizational tools allowed us to rapidly improve the usability, understandability, and usefulness of CDS in a generalizable sample of practicing nurses. CONCLUSIONS: The method outlined allows the rapid integration of nursing terminology based electronic health record data into routine workflow and holds strong potential for improving patient outcomes. IMPLICATIONS FOR NURSING PRACTICE: The methods and organizational tools for development of multiple CDS system features can be used to translate knowledge into practice.